1989
DOI: 10.1007/bf00247939
|View full text |Cite
|
Sign up to set email alerts
|

Neck muscle activation patterns in humans during isometric head stabilization

Abstract: A musculoskeletal system with more muscles than there are motions could be programmed in alternative ways to produce a single movement. In this case, the muscles would have the potential to be maximally responsive in multiple directions rather than responding preferentially in a single direction. To determine the response patterns of muscles in the head-neck motor system, the simultaneous activation of four of the 23 neck muscles acting on the head was recorded with both surface and intramuscular electrodes. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
62
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(71 citation statements)
references
References 16 publications
7
62
2
Order By: Relevance
“…Second, although the pattern of muscle activation in each cat was consistent within a task, axes of maximal activation differed between the reflex and voluntary responses (e.g., splenius exhibited greater activation in the pitch and roll rotations during voluntary tracking, and in the yaw and pitch rotations during reflex testing). Third, as found in decerebrate cats (Baker and Wickland 1988) and humans (Keshner et al 1989), the best excitation of the muscle was not always in the plane that would produce a maximum mechanical advantage for the muscle based on its line of pull.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Second, although the pattern of muscle activation in each cat was consistent within a task, axes of maximal activation differed between the reflex and voluntary responses (e.g., splenius exhibited greater activation in the pitch and roll rotations during voluntary tracking, and in the yaw and pitch rotations during reflex testing). Third, as found in decerebrate cats (Baker and Wickland 1988) and humans (Keshner et al 1989), the best excitation of the muscle was not always in the plane that would produce a maximum mechanical advantage for the muscle based on its line of pull.…”
Section: Discussionmentioning
confidence: 96%
“…The cervicocollic reflex (CCR) also counteracts unplanned head movements, but as a result of movements of the head relative to the trunk which stimulate proprioceptive inputs at the neck . Descending signals can occur prior to movement as preprogrammed motor commands, or can modify stimulus-response relations according to the specific task constraints (Guitton et al 1986;Keshner et al 1989). Finally, head position is influenced by biomechanical forces arising within the head-neck motor plant which has a unique morphology with its inertial mass sitting atop a flexible column composed of multiple joints and ligaments (Vidal et al 1986).…”
Section: Introductionmentioning
confidence: 98%
“…Healthy individuals exhibit different preferred activation of the splenius as a neck extensor or flexor , Keshner et al 1989, synchronized neuronal drive between deep and superficial muscles , and different activation strategies among individuals during a reflexive task ). Individuals with WAD had less defined activity in the deep semispinalis capitis (Schomacher et al 2012) and higher activity in the superficial neck extensor has been reported (Juul-Kristensen et al 2013), but when controlling for movement velocity, the acceleration or deceleration peak in the splenius was not different from that of healthy controls (Vikne et al2013).…”
Section: Discussionmentioning
confidence: 99%
“…Different EMG tests result in different neck muscle activation patterns; if the head is firmly clamped and force applied to the head, preferred activation was seen in the neck muscles except for the splenius capitis (Keshner et al 1989, whereas more individual muscle responses occur during reflexive movements ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation